μPADs for Chemistry Education and Acetic Acid Analysis: A Literature Review - Medardus Josua Petrus Tosang; Masriani; Firman Shantya Budi (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Microfluidic paper-based analytical devices (μPADs) have emerged as promising analytical platforms due to their low cost, portability, simplicity, and minimal reagent requirements. These characteristics make μPADs attractive for both chemical analysis and chemistry education, particularly in laboratory activities that emphasize sustainable and environmentally friendly practices. This literature review aims to examine the development and application of μPADs in chemistry learning and acetic acid determination through acid–base titration experiments. A descriptive literature review with a qualitative approach was conducted using articles published between 2016 and 2025. Relevant literature was identified through Google Scholar, ScienceDirect, PubMed, and ACS Publications using keywords related to μPADs, chemistry education, acid–base titration, and acetic acid analysis. Following a screening and eligibility assessment process, 21 peer-reviewed articles were selected and analyzed using qualitative content analysis. The findings indicate that μPADs serve not only as analytical tools but also as instructional media that support the understanding of acid–base reactions, stoichiometry, limiting reagents, and titration concepts through microscale experimentation. In acetic acid analysis, distance-based and colorimetric μPADs integrated with smartphone-assisted image processing provide results comparable to conventional titration methods while reducing reagent consumption, analysis time, and chemical waste generation. The integration of digital image analysis also introduces students to modern analytical techniques and enhances digital literacy skills. Despite challenges related to fabrication standardization and analytical reproducibility, μPADs demonstrate considerable potential for implementation in higher education laboratories as cost-effective and sustainable tools that support green analytical chemistry practices.